PENGARUH PUPUK HAYATI DAN DOSIS AZOTOBACTER SP. DALAM FITOREMEDIASI MENGGUNAKAN TANAMAN RAMI (BOEHMERIA NIVEA L. GAUD) PADA TANAH TERCEMAR HIDROKARBON MINYAK BUMI - Gea Anggun Pratiwi; Diyan Herdiyantoro; Pudjawati Suryatmana (Jurnal Teknologi Pertanian Andalas, 2018)
Phytoremediation in soil contaminated with petroleum hydrocarbon is a technology to remediate contaminant using plant as nutrient availability facilitator for degrading microbials in the rhizosphere. Phytoremediation can be promoted by biofertilizers containing nitrogen fixer, phosphate solubilizer, and mychorrizal for improving soil fertility, also Azotobacter sp. which produces biosurfactant. The purpose of this research was to determine the effects of biofertilizers and doses of Azotobacter sp. on enhancing of petroleum hydrocarbon biodegradation efficiency, nitrogen fixing bacteria and phosphate solubilizing bacteria population, and total chlorophyll content in ramie leaves. This research was carried out from September 2016 to April 2017 at Laboratory of Soil Biology, Laboratory of Soil Fertility and Plant Nutrition, also Greenhouse and Field Station Faculty of Agriculture Universitas Padjadjaran. This research used factorial randomized complete block design with two factors consisted of biofertilizers (control, nitrogen fixing bacteria, phosphate solubilizing bacteria, phosphate solubilizing fungi, mychorrizal, and biofertilizer consortium) and doses of Azotobacter sp. (control, 1%, and 2%). The results of experiment showed there was an interaction effect between biofertilizer of phosphate solubilizing fungi and 2% dose of Azotobacter sp. on the enhancement of total chlorophyll content in ramie leaves.